Determine Entrepreneurial Characteristics Using Mobile Android Game Freezer - Ismail, Mohammad; Ibrahim, Ahmad Fuad; Yaacob, Mohd Rafi; Ibrahim, Asrul Hey; Zakaria, Mohd Nazri; Razak, Razli Che; Yusoff, Mohd Nor Hakimin; Guan, Tan Tse; Kamaruddin, Anis Nabila (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Psychometric Test has been used as an individual trait measurement for a long time for both experienced entrepreneurs as well as young generation who are looking for their potential in entrepreneurship. The assessment and measurement of strength and weaknesses of key entrepreneurial traits provides the entrepreneurial level and personal development planning for entrepreneur or those who want to venture into business. However, the traditional psychometric test lacks of fun element which is less enjoyable activity during answering the test. Furthermore, it requires basic understanding of business jargon that difficult for certain respondents to provide accurate respond. The purpose of this study is to propose a gamification approach which is mobile game application called ‘Freezer’ that can measured entrepreneurial traits of the player. In this sense, ‘Freezer’ creates a simulated scenario for respondents to play as an ice cream business owner and to win as a successful business person, each action done will be measured as entrepreneurial traits criteria. At the end of the game, the result will be presented that can describe the entrepreneurial characteristics of the individuals based on their planning and activities during playing the game.